A Framework for Interdisciplinary Research Methodology in Agroforestry: A Review - Buyinza, Joel; Sekatuba, Jude; Kalanzi, Fred (East African Nature and Science Organization, 2025)
This paper provides a framework for interdisciplinary research (IDR) methodology in agroforestry, motivated by a general belief that by drawing information from different fields and employing different methodologies, a broad understanding of an existing issue can be achieved. Literature from four scientific paradigms was reviewed to recommend a suitable paradigm for IDR in agroforestry. We promote a pluralistic approach around the concept of ‘what works’ such that agroforestry research and extension focus on applications of techniques to solve a problem. The study suggests a framework for IDR in the context of developing countries by modifying an existing Methodology for Interdisciplinary Research (MIR) framework that was developed to help cross disciplinary borders, especially those between the natural sciences and the social sciences. The existing framework is however limited to real-life applications in teaching and research. We contend that agroforestry research should be seen to benefit the rural poor, foster innovation and farm productivity to feed the growing world population and help farmers adapt to the changing climate. The suggested IDR framework therefore caters for extension and feedback mechanisms, that appear to be the missing link between research and education. The new framework further provides for social relevance and the generation of data for informing policy decisions relating to sustainable agriculture. The paper also highlights the main barriers and opportunities for implementing IDR in agroforestry. The current and future global complex agricultural challenges require experts with interdisciplinary experience. Therefore, interdisciplinary research in agroforestry must increasingly become the standard rather than the exception because the approaches needed and the implications of agroforestry research are by their very nature interdisciplinary.